Optimal Risk Adjustment in Markets with Adverse Selection: An Application to Managed Care - Glazer, Jacob; McGuire, Thomas G (American Economic Review, 2000)
Optimal Risk Adjustment in Markets with Adverse Selection: An Application to Managed Care by Jacob Glazer and Thomas G. McGuire. Published in volume 90, issue 4, pages 1055-1071 of American Economic Review, September 2000